Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2001
DOI: 10.1093/jac/48.6.911
|View full text |Cite
|
Sign up to set email alerts
|

Comparative activity of linezolid and other new agents against methicillin-resistant Staphylococcus aureus and teicoplanin-intermediate coagulase-negative staphylococci

Abstract: The activity of linezolid was determined against 225 recently isolated methicillin-resistant Staphylococcus aureus (MRSA) and 20 methicillin-resistant coagulase-negative staphylococci (CoNS) with decreased levels of susceptibility to teicoplanin. Linezolid activity was compared with other new agents (quinupristin-dalfopristin, trovafloxacin, moxifloxacin, levofloxacin and telithromycin) and six other antimicrobials (erythromycin, clindamycin, gentamicin, vancomycin, teicoplanin and rifampicin). The in vitro ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0
2

Year Published

2003
2003
2013
2013

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 8 publications
0
22
0
2
Order By: Relevance
“…Based on these results, daptomycine appears to be a good therapy option for infections caused by these bacteria. Similarly, in a study by Betriu et al (2001), linezolid was found to be potentially useful in the treatment of infections caused by MRSA and for MRCNS strains that have decreased sensitivity to teicoplanin [3].…”
Section: Discussionmentioning
confidence: 94%
“…Based on these results, daptomycine appears to be a good therapy option for infections caused by these bacteria. Similarly, in a study by Betriu et al (2001), linezolid was found to be potentially useful in the treatment of infections caused by MRSA and for MRCNS strains that have decreased sensitivity to teicoplanin [3].…”
Section: Discussionmentioning
confidence: 94%
“…Multiple in vitro and in vivo studies have demonstrated that linezolid is either more potent or as active in the eradication of Gram-positive cocci when compared with traditional antimicrobial agents such as vancomycin or other novel antibiotics, eg, quinupristin-dalfopristin (27)(28)(29). The causes for its superior efficacy compared to vancomycin are yet to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…The causes for its superior efficacy compared to vancomycin are yet to be determined. Both vancomycin and linezolid have similar halflives of 6 to 8 h (21,(29)(30) and postantibiotic effects of 1 to 2 h (31,32). Vancomycin has lower minimum inhibitory concentrations for many Gram-positive cocci compared with linezolid.…”
Section: Discussionmentioning
confidence: 99%
“…10 In vitro, linezolid, quinupristin-dalfopristin, moxifloxacin and trovafloxacin, which are new antibiotics, reveal good activity against MRSA and methicillin-resistant and teicoplaninintermediate coagulase negative staphylococci. 11 In particular, linezolid has an acceptable safety profile for both i.v. and oral administration and has proven effective in the treatment of infections caused by methicillin-resistant staphylococcal species in critically ill patients.…”
Section: Discussionmentioning
confidence: 99%